2017
DOI: 10.3390/su9071210
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Correlations between Corporate Giving, Performance and Company Value

Abstract: The paper seeks to identify the relationship between the charitable contributions, performance, and market value of Romanian listed companies. To achieve the objective, a panel data analysis was conducted on a group of companies listed at Bucharest Stock Exchange in the period 2011 to 2016, which registered profit for the entire period. The empirical analysis points out, using a logistic regression, which financial and non-financial indicators contribute to the decisions of the companies to make the charitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 71 publications
(62 reference statements)
0
35
1
Order By: Relevance
“…This finding is consistent with previous researches into CSR and firm financial performance linkages, which found positive effects of CSR [24][25][26]36]. The finding is also consistent with related studies in the context of emerging economies [27,37,38], and related studies in the context of M&A [3]. However, our results are not consistent with previous studies that suggest CSR has a negative effect on performance [18,19].…”
Section: Effects Of Csr On Long-term Manda Performancecontrasting
confidence: 55%
See 1 more Smart Citation
“…This finding is consistent with previous researches into CSR and firm financial performance linkages, which found positive effects of CSR [24][25][26]36]. The finding is also consistent with related studies in the context of emerging economies [27,37,38], and related studies in the context of M&A [3]. However, our results are not consistent with previous studies that suggest CSR has a negative effect on performance [18,19].…”
Section: Effects Of Csr On Long-term Manda Performancecontrasting
confidence: 55%
“…The study found that fulfilling CSR is beneficial to improving a firm's value. Recently, Hategan and Ruxandra Ioana (2017) [37] adopted panel data from Romanian listed companies, from 2011 to 2016. This study found that CSR behaviors such as charitable contributions have a positive influence on corporate performance.…”
Section: Csr and Long-term Manda Performancementioning
confidence: 99%
“…Hategan and Curea-Pitorac [14] find a positive correlation between CSR (i.e., corporate giving) and firm value (measured as Tobin's Q). In a similar vein, Lenz et al [15] find a positive correlation between CSR and firm value (measured as Tobin's Q).…”
Section: Univariate Analysismentioning
confidence: 97%
“…Thus, CSR is becoming important in both academia and practice [2][3][4][5][6]. A number of studies suggest that CSR is positively related to firm value [2,4,[7][8][9][10][11][12][13][14][15][16][17][18][19]. Some studies even find a negative relationship between CSR and firm value [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As such, entity's performance is an important factor in determining the environmental information to be disclosed. Many studies have used return on equity (ROE) and/or return on assets (ROA) to express company performance [58][59][60][61][62][63][64][65][66]. We have used ROE (net profit/equity) to accomplish our goal.…”
Section: Company Performancementioning
confidence: 99%